Implementasi Gerakan Go-Green di Kelompok PKK RT 01 RW 08, Kelurahan Tembalang Semarang : Pelatihan Pembuatan Pembersih Lantai dari Limbah Minyak Jelantah - Ery Fatarina P; Retno Ambarwati SL; Atika Mutiarachim; Bayu Ariyanto; Irfiana Dwi Rahmawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service program was designed to empower the women’s group PKK RT 01 RW 08 in Tembalang, Semarang, through education and innovation in processing used cooking oil into eco-friendly floor cleaner. Household cooking oil waste, commonly known as “jelantah,” is often discarded and contributes to environmental pollution, while in fact it can be reused as a valuable resource. The program aimed not only to provide technical skills but also to increase environmental awareness and promote sustainable household practices. The implementation took place over three months (June–August 2025) using a participatory approach that included socialization, training, mentoring, and evaluation. During the activities, participants were introduced to the principles of green chemistry, practiced step-by-step floor cleaner production, and learned packaging and digital marketing techniques. As a result, the group successfully produced 65 bottles of “Lely Eco Floor” cleaner (260% of the initial target), distributed them for household use, and established an environmental movement group named “Lely Bersih Lestari.” Pre- and post-test scores indicated significant improvement in participants’ knowledge and skills. The program brought multiple impacts: reducing oil waste pollution, enhancing social cohesion, and opening opportunities for micro-scale entrepreneurship. Overall, this activity demonstrates how simple technology and community engagement can support sustainable development and women’s empowerment at the grassroots level.